Reproductive relationships between taxa morphologically close to Elymus caninus (Poaceae: Triticeae) - E. V. Shabanova; A. V. Agafonov; O. V. Dorogina (Вавиловский журнал генетики и селекции, 2024)
A hybridological study of biotypes of species close to Elymus caninus: E. prokudinii, E. viridiglumis, E. goloskokovii, as well as a number of morphologically deviant biotypes in Russia and Kazakhstan, was carried out. The objectives were to study the levels of reproductive relationships and the degree of integration of the species E. goloskokovii, E. prokudinii, and E. viridiglumis into the E. caninus complex. Our estimates of the seed fertility of natural parental biotypes were within 60–90 %. Among the combinations of crossing in F1, the highest seed setting was found in the hybrids formed by parental pairs from close habitats, regardless of the taxonomic rank of biotypes. The highest fertility values (55.6 and 46.1 %) were found in combinations involving E. caninus, E. viridiglumis and E. goloskokovii. It has been concluded that the biotypes of these species included in sexual hybridization form a single recombination gene pool, within which slight differences in reproductive compatibility are observed. The nature of the inheritance of the diagnostic features of lemmas“presence of trichomes” and“length of awns”, according to the digenic and monogenic type, respectively, is shown. The high seed fertility of the created hybrids and the presence of intermediate forms in the F2 generation according to distinctive features indicate the possibility of interspecific introgression when species grow together in natural populations. Thus, the assessment of the inheritance of diagnostic characters makes it possible to classify E. goloskokovii, E. prokudinii, and E. viridiglumis as intraspecific taxa of E. caninus s. l. Data were obtained on the morphological and reproductive properties of interspecific hybrids with the participation of the species E. mutabilis as a possible donor in the speciation of taxa close to E. caninus. In cross combinations of E. caninus × E. mutabilis and E. mutabilis × E. caninus, lower values of seed fertility of hybrids in the F1 and F2 generations were noted compared to hybrids between the species E. caninus, E. goloskokovii, E. prokudinii and E. viridiglumis. Nevertheless, on the basis of chorological and morphological criteria, we concluded that E. caninus and E. mutabilis are independent species.